Time Management: Strategy of Students’ Preparation for Examinations without Emergency Rush - M. A. Lukashenko; T. V. Telegina (Высшее образование в России)
Today practically all students pursuing higher education are obliged to earn money simultaneously and this takes most of their time. In such circumstances in order to prepare for studies and especially for examinations students usually have too little time left. Moreover, they tend to overestimate its amount and unrealistically plan time needed to prepare for exams that inevitably and adversely affect quality of their education. The problem of optimizing students’ preparations for examinations acquires more and more theoretic and practical importance. The purpose of this work is to identify how much it is possible to increase the effectiveness of students’ preparations for studies and examinations by applying time management tools in “learning by doing” mode. For that the article provides a description of the research conducted in groups having day and evening classes and devoted to practical implementation of time management tools such as time-keeping, flexible planning, work with time absorbents. Research method consisted in oral surveys, time-keeping and analyzing its results, optimizing time planning with the help of fighting with time absorbents technics and revealing its real amount to achieve the objective of preparation for examinations. The article works out and proves the algorithm of calculating the real resource of time needed to prepare for examinations, that was tested in student groups and showed its effectiveness on the basis of the examinations’ results.